A Decoupled Spherical Parallel Mechanism with Sphere Workspace and Its Characteristic - Li Xiang; Li Weimin; Feng Shaohui; Zhang Jianjun; Yu Shanshan (Jixie chuandong)
Aiming at the workspace of existing spherical parallel mechanism is smaller in the field of large spherical workspace application,a decoupling spherical parallel mechanism with sphere workspace is proposed.Firstly,according to the limitation from the friction circle of the revolute joint,the modified mechanism is given,which can provide a sphere workspace,and its number of degree of freedom is analyzed. Secondly,the inverse and forward position for the mechanism is derived with the closed vector method. The expression of the Jacobian matrix is deduced with the relational expression between the input and output parameters of the mechanism. And according to the expression of the Jacobian matrix,the decoupled feature of the proposed parallel mechanism is validated. The theoretical foundation for the application of the mechanism to the sphere workspace is provided.